Experimental evaluation and statistical modeling of kenaf fiber-reinforced geopolymer concrete - Noor Abbas, Al-Ghazali; Abdul Aziz, Farah Nora Aznieta; Abdan, Khalina; Mohd Nasir, Noor Azline; Fahim Huseien, Ghasan (Elsevier, 2023)
Sustainable construction materials are in needs to reduce CO2 emissions in the environment. Geopolymer being an emergent sustainable construction material had been extensively studied. However, its brittleness is still the main issue to be overcome. Hence, in this research, natural kenaf fiber (KF) as environmental-friendly low-cost material is introduced to enhance the overall quality of the geopolymer. This study introduces a potential sustainable construction material called Kenaf Fiber-Reinforced Geopolymer Concrete (KFRGC) which is studied via experimental tests and statistical modelling. The effects of 20 mm to 40 mm lengths and 0.75 % to 1.5 % volume fractions of kenaf fibers on the engineering properties of KFRGC were measured. The splitting tensile strength and flexural strength of KFRGC were observed to improve without any significant increase in the compressive strength. At 28 days of curing age, KFRGC prepared with 30 mm long, and 1.25 % volume fraction of fiber showed a 20 % and 27 % increase in splitting tensile strength and flexural strength, respectively, compared to the plain geopolymer. Furthermore, the model predicted and experimental results closely matched (less than 5 % inaccuracy). It is concluded that natural KF-included concrete can be used as an eco-friendly and sustainable building material. However, the durability aspect must be studied before it can be commercially used.